Adoption of the budget by competence in Brazil based on comparative experiences in the USA, Canada, United Kingdom, Australia, and New Zealand - Gonçalves, Andrew Pereira; Nascimento, Roberto Sérgio do; Viotto, Ricardo (REVISTA AMBIENTE CONTÁBIL - Universidade Federal do Rio Grande do Norte - ISSN 2176-9036, 2025)
Purpose: To analyze the feasibility of adopting competency budgeting in Brazil. Methodology: Qualitative, exploratory, bibliographic, documental, and content analysis nature, with the cataloguing of the material based on environmental attributes (political commitment, human capital, long-term sustainability, and macroeconomic policy) and technical attributes (depreciation and valuation of assets, capital expenditure, symmetry between reports, recognition of benefits and accountability). The work is comparative in nature based on the practices adopted in the USA, Canada, United Kingdom, Australia, and New Zealand. Results: The examinations of environmental attributes in comparison with technical attributes were more homogeneous in reference to the countries analysed. It was identified that the technical attributes were the ones that were more casuistic, aiming to meet the specific situations of the participating countries. In Brazil, if the reform were implemented, the study pointed to attributes related to macroeconomic (environmental) policy and accountability (technical) as being the most favorable. Contributions of the Study: It was identified that the most advanced experiences on accrual budgeting come from countries of Anglo-Saxon origin, whose accounting systems are convergent with those used by companies. In this sense, it is hoped that the work can contribute to the broadening of the discussion of the systematics, in view of the indication of environmental and technical attributes considered to facilitate and/or hinder the process.